Partner outcomes from an uncontrolled trial of Couple HOPES: A guided online couple intervention for posttraumatic stress disorder and relationship enhancement. Issue 1 (18th September 2022) - Crenshaw, Alexander O.; Whitfield, Kristen M.; Collins, Alexis; Valela, Robert; Varma, Sonya; Landy, Meredith S. H.; Ip, Jennifer; Donkin, Victoria; Earle, Elizabeth; Siegel, Ashley; Samonas, Christina; Bushe, Julianne; et al.
Abstract: Posttraumatic stress disorder (PTSD) is associated with significant individual and relationship impairment for people with PTSD and their romantic partners. Conjoint treatments, such as cognitive behavioral conjoint therapy for PTSD (CBCT), are designed to address individual and relationship factors, yet significant barriers impede accessing in‐person therapy. Couple HOPES (i.e., Helping Overcome PTSD and Enhance Satisfaction) is a coach‐guided, online couple intervention for PTSD based on CBCT that was designed to address these barriers. Previous investigations have found preliminary efficacy of Couple HOPES for improving PTSD symptoms, relationship functioning, and some individual functioning domains for the partner with probable PTSD. However, no study to date has tested individual outcomes for romantic partners, which is needed to fully evaluate the intervention's promise. The current study tested these partner outcomes in a combined, uncontrolled sample of 27 couples. Intent‐to‐intervene analyses found significant improvements at postintervention in four of eight tested outcomes, including ineffective arguing, g = 0.74; anger, g = 0.32; perceived health, g = 0.67; and quality of life, g = 0.56. Depressive symptoms, generalized anxiety, alcohol misuse, and work functioning did not significantly change, g s = 0.17–0.42. Among participants who completed a 1‐month follow‐up assessment, generalized anxiety, g = 0.43, and perceived health, g = 0.73, significantly improved over follow‐up, whereas anger, g = ‐0.48, lost gains previously made. Results were largely consistent in the completer sample. These findings show the potential of Couple HOPES to have broad benefits not only for individuals with probable PTSD but also for their romantic partners.